2016
DOI: 10.1111/acem.12920
|View full text |Cite
|
Sign up to set email alerts
|

Association of Guideline‐concordant Acute Asthma Care in the Emergency Department With Shorter Hospital Length of Stay: A Multicenter Observational Study

Abstract: Objectives: The objectives were to determine whether guideline-concordant emergency department (ED) management of acute asthma is associated with a shorter hospital length of stay (LOS) among patients hospitalized for asthma.Methods: A multicenter chart review study of patients aged 2-54 years who were hospitalized for acute asthma at one of the 25 U.S. hospitals during 2012-2013. Based on level A recommendations from national asthma guidelines, we derived four process measures of ED treatment before hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…5 An observational study of 854 patients showed a significant reduction in the hospital LOS for patients managed via an asthma pathway compared to those who were not, independent of the quality of inpatient asthma care. 23 Our intervention not only resulted in a reduction in ED LOS but also led to a reduction in the admission rate of those children who were clinically well at the 1-h assessment. This may be partially explained by the results of a previous study which found that the duration of observation in ED is directly related to the likelihood of hospital admission.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…5 An observational study of 854 patients showed a significant reduction in the hospital LOS for patients managed via an asthma pathway compared to those who were not, independent of the quality of inpatient asthma care. 23 Our intervention not only resulted in a reduction in ED LOS but also led to a reduction in the admission rate of those children who were clinically well at the 1-h assessment. This may be partially explained by the results of a previous study which found that the duration of observation in ED is directly related to the likelihood of hospital admission.…”
Section: Discussionmentioning
confidence: 82%
“…The authors reported a reduction of 30 min in both ED LOS and time to inpatient bed request with the implementation of a standard asthma pathway with clear admission criteria . An observational study of 854 patients showed a significant reduction in the hospital LOS for patients managed via an asthma pathway compared to those who were not, independent of the quality of inpatient asthma care …”
Section: Discussionmentioning
confidence: 98%
“…When indicated by symptoms or physical findings (eg, fever, localized adventitious lung sounds, hypoxemia, or vomiting), initiating such interventions in the ED may shorten length of stay by 6 to 10 hours. 19,20 If this is the case, then there could be opportunities for improvement by incorporating evidencebased care algorithms in the ED, given the marked variations among the OPAR hospitals. Indeed, the use of validated assessment tools or development of more sensitive scores could expedite the identification of children with more severe illnesses who would benefit from an earlier initiation of treatments.…”
Section: Opportunities For Process Improvement By Sitementioning
confidence: 99%
“…10 The design, setting, and methods of data collection used in the study have been reported previously. [11][12][13][14] Briefly, we recruited hospitals by primarily inviting sites that had participated in the University HealthSystem Consortium Asthma Clinical Benchmarking Project that evaluated patients hospitalized for asthma exacerbation during 1999 to 2000. 5 A total of 25 urban teaching hospitals across 18 U.S. states completed the current 37th Multicenter Airway Research Collaboration study ( Supplemental Table E1).…”
Section: Design Setting and Participantsmentioning
confidence: 99%